Law and Religious Minorities in Medieval Societies between theory and praxis - Tolan, John; Echevarria, Ana; Pedro Monferrer-Sala, Juan (Religion and Law in Medieval Christian and Muslim Societies, 2016)
This volume shows through the use of legal sources that law was used to try to erect boundaries between communities in order to regulate or restrict interaction between the faithful and the non-faithful; and at the same time shows how these boundaries were repeatedly transgressed and negotiated. Muslim law developed a clear legal cadre for dhimmīs, inferior but protected non-Muslim communities (in particular Jews and Christians) and Roman Canon law decreed a similar status for Jewish and Muslim communities in Europe. Yet the theoretical hierarchies between faithful and infidel were constantly brought into question in the daily interactions between men and women of different faiths in streets, markets, bath-houses, law courts, etc. The twelve essays in this volume explore these tensions and attempts to resolve them. These contributions show that law was used to try to erect boundaries between communities in order to regulate or restrict interaction between the faithful and the non-faithful-and at the same time how these boundaries were repeatedly transgressed and negotiated. These essays explore also the possibilities and the limits of the use of legal sources for the social historian.